Hypergeometric τ Functions of the q-Painlevé Systems of Types A⁽¹⁾₄ and (A₁+A′₁)⁽¹⁾ - Nakazono, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We consider q-Painlevé equations arising from birational representations of the extended affine Weyl groups of A⁽¹⁾₄- and (A₁+A₁)⁽¹⁾-types. We study their hypergeometric solutions on the level of τ functions.